(untitled) (Journal of Dhaka National Medical College & Hospital, 2012)
Urinary tract infections (UTIs) are some of the most common infections experienced by human. It is also the most common cause of nosocomial infections in adults. The aim of this study was to determine the bacteriological pattern and their sensitivity to commonly used antimicrobial drugs in urinary tract infection in Bangladesh. This was a prospective study conducted in Microbiology department of Dhaka National Medical College, a tertiary level teaching hospital in Dhaka, Bangladesh. A total of 216 culture positive urine samples were examined. Female patient were found to be more 65.7% than male 34.3%. Maximum patients were from 20-35 yrs. age group. The most common isolate was E.coli 84.3%. These E.coli is more sensitive to Imipenem 93.98%, Amikacin 90.52%, Nitrofurantoin 78.88% Ceftazidim 78.26%, Ciprofloxacin 70.67%, Cefuroxime 65.49%,Ofloxacin 60.83%, Ceftriaxone 59.03% and Cephradin 56.96%. Resistance is more in case of amoxicillin 82.41%, Doxycycline 72.42%, Cefixime 58.70% and Nalidixic Acid 57.02%. DOI: http://dx.doi.org/10.3329/jdnmch.v17i1.12186 J. Dhaka National Med. Coll. Hos. 2011; 17 (01): 18-21